PENGARUH SISTEM PENGENDALIAN INTERNAL, WHISTLEBLOWING SYSTEM DAN GOOD CORPORATE GOVERNANCE TERHADAP PENCEGAHAN FRAUD DENGAN MORALITAS INDIVIDU SEBAGAI VARIABEL MODERASI (STUDI EMPIRIS PADA BANK DI KOTA AMBON) - Saiselar, Stenly Rival; Atarwaman, Rita J. D.; Usmany, Alfrin Ernest Marthen (Jurnal Akuntansi, 2024)
This research aims to empirically test the influence of the internal control system, Whistleblowing System and Good corporate governance on fraud prevention, as well as test whether individual morality is able to moderate the internal control system, Whistleblowing System and Good corporate governance on fraud prevention. The sample in this study was 37 bank employees at Bank BRI, BTN, Mandiri and BPD Maluku. The sampling technique uses Pruposive Sampling by determining samples based on certain criteria. Data analysis techniques use SPSS 23 software. The research results show that the internal control system, Whistleblowing System and Good corporate governance have no effect on fraud prevention. while individual morality is able to moderate the influence of the internal control system, Whistleblowing System and Good corporate governance on fraud prevention.